Simultaneous biosynthesis of (R)-acetoin and ethylene glycol from D-xylose through in vitro metabolic engineering - Jia, Xiaojing; Kelly, Robert M.; Han, Yejun (Metabolic engineering communications, 2018)
(R)-acetoin is a four-carbon platform compound used as the precursor for synthesizing novel optically active materials. Ethylene glycol (EG) is a large-volume two-carbon commodity chemical used as the anti-freezing agent and building-block molecule for various polymers. Currently established microbial fermentation processes for converting monosaccharides to either (R)-acetoin or EG are plagued by the formation of undesirable by-products. We show here that a cell-free bioreaction scheme can generate enantiomerically pure acetoin and EG as co-products from biomass-derived D-xylose. The seven-step, ATP-free system included in situ cofactor regeneration and recruited enzymes from Escherichia coli W3110, Bacillus subtilis shaijiu 32 and Caulobacter crescentus CB 2. Optimized in vitro biocatalytic conditions generated 3.2 mM (R)-acetoin with stereoisomeric purity of 99.5% from 10 mM D-xylose at 30 °C and pH 7.5 after 24 h, with an initial (R)-acetoin productivity of 1.0 mM/h. Concomitantly, EG was produced at 5.5 mM, with an initial productivity of 1.7 mM/h. This in vitro biocatalytic platform illustrates the potential for production of multiple value-added biomolecules from biomass-based sugars with no ATP requirement. •Novel and unnatural in vitro metabolic pathway was constructed for (R)-acetoin and ethylene glycol biosynthesis from D-xylose.•The ATP-free, cell-free reaction system achieved enantioselective synthesis with in situ cofactor regeneration.•Under optimized condition 99.2% of D-xylose was consumed and produced chiral (R)-acetoin with stereoisomeric purity of 99.5%.